Debt financing and firm performance: empirical evidence from the Pakistan Stock Exchange - Aamir Nazir; Muhammad Azam; Muhammed Usman Khalid (Emerald Publishing Limited, 2021)
The purpose of this study is to investigate the relationship between the listed firms' debt level and performance on the Pakistan Stock Exchange (PSX) during a five-year period.This study uses pooled ordinary least squares regression and fixed- and random-effects models to analyse a cross-sectional sample of 30 Pakistani companies operating in the automobile, cement and sugar sectors during 2013â€“2017 (NÂ =Â 150).The results indicate that both short- and long-term debt have negative and significant impacts on firm performance in profitability. This suggests that agency issues may lead to a high-debt policy, resulting in lower performance. However, both sales growth and firm size have positive effects on the profitability of non-financial sector companies.This study suggests that when debt financing significantly and negatively influences firm profitability, company owners and managers should focus on finding a satisfactory debt level. However, this study is limited to the automobile, cement and sugar sectors of Pakistan. Future studies could address other sectors, such as textiles, fertilizers and pharmaceuticals.This study focusses on enhancing the existing empirical knowledge of debt financing's influence on the PSX's major sectors' profitability.